Histiocytic Sarcoma with Central Nervous System Involvement in Dogs: 19 Cases (2006–2012). (25th February 2015) - Mariani, C.L.; Jennings, M.K.; Olby, N.J.; Borst, L.B.; Brown, J.C.; Robertson, I.D.; Seiler, G.S.; MacKillop, E.
Abstract : Background: Reports of histiocytic sarcoma (HS) involving the central nervous system (CNS) are sparse and consist mainly of case reports describing 1–3 animals. Objective: The objective of this study was to report the signalments, clinical signs, clinicopathologic and diagnostic imaging findings, treatment, and outcome of a series of dogs with HS and CNS involvement. Animals: Nineteen dogs with HS examined at veterinary referral hospitals. Methods: Retrospective case series. Medical records were reviewed and cases with a histopathological diagnosis of CNS HS were included in the study. Diagnostic imaging studies of the CNS were evaluated and histopathologic samples were reviewed to confirm the diagnosis. Results: Retrievers and Pembroke Welsh Corgis were overrepresented in this cohort of dogs. Tumors involved the brain in 14 dogs and the spinal cord in 5. In 4 dogs, HS was part of a disseminated, multiorgan process whereas it appeared confined to the CNS in 15 dogs. Diagnostic imaging had variable appearances although extraaxial masses predominated in the brain. There was meningeal enhancement in all dogs that was often profound and remote from the primary mass lesion. Pleocytosis was present in all dogs with CSF evaluation. Median survival was 3 days. Conclusions and Clinical Importance: Breed predispositions appear to vary from reports of HS in other organ systems. Some unique imaging and clinicopathologic characteristics, particularly brain herniation, profound meningeal enhancement, and pleocytosis in combination with 1 or more mass lesions, might help to differentiate this neoplasm from others involving the CNS, although this requires further study.